The SAGE handbook of popular music - Bennett, Andy 1963-; Waksman, Steve (SAGE Publications Limited, 2015)
"The SAGE Handbook of Popular Music provides a highly comprehensive and accessible summary of the key aspects of popular music studies. The text is divided into 9 sections: Theory and Method; The Business of Popular Music; Popular Music History; The Global and the Local; The Star System; Body and Identity; Media; Technology; and, Digital Economies. Each section has been chosen to reflect both established aspects of popular music studies as well as more recently emerging sub-fields. The handbook constitutes a timely and important contribution to popular music studies during a significant period of theoretical and empirical growth and innovation in the field. This is a benchmark work which will be essential reading for educators and students in popular music studies, musicology, cultural studies, media studies and cultural sociology."--Publisher's description.